Fibrinogen alpha chain promotes the migration and invasion of human endometrial stromal cells in endometriosis through focal adhesion kinase/protein kinase B/matrix metallopeptidase 2 pathway. Issue 4 (22nd July 2020) - Li, Hui; Ma, Rui-Qiong; Cheng, Hong-Yan; Ye, Xue; Zhu, Hong-Lan; Chang, Xiao-Hong
Abstract: Fibrinogen alpha chain (FGA), a cell adhesion molecule, contains two arginyl-glycyl-aspartic acid (RGD) cell adhesion sequences. Our previous study demonstrated that FGA, as an up-regulated protein in endometriosis (EM), was closely related to disease severity and involved in the development of EM. However, the biological functions and underlying mechanism of FGA in EM have not been fully understood. To explore the roles of FGA in EM, we analyzed the effects of FGA on the biological behaviors of human primary eutopic endometrial stromal cells (EuESC). The results indicated FGA knockdown suppressed the migration and invasion ability of EuESC, which also altered the distribution of cytoskeletal filamentous and cell morphology. Western blot analysis demonstrated that knockdown of FGA attenuated the migration-related protein levels of vimentin and matrix metallopeptidase 2 (MMP-2), but not integrin subunit alpha V (ITGAV) and integrin subunit beta 3 (ITGB3). Meanwhile, integrin-linked transduction pathways were detected. We found FGA knockdown significantly suppressed the expression of focal adhesion kinase (FAK) level and protein kinase B (AKT) phosphorylation, without extracellular-signal-regulated kinase (ERK) dependent pathways. Treatment with the AKT inhibitor MK2206 or RGD antagonist highly decreased the effects of FGA on the migration and invasion of EuESC. RGD antagonist treatment strongly inhibited FAK- and AKT-dependent pathways, but not ERK pathways. Our data indicated that FGA may enhance the migration and invasion of EuESC through RGD sequences binding integrin and activating the FAK/AKT/MMP-2 signaling pathway. This novel finding suggests that FGA may provide a novel potential approach to the treatment of EM, which provides a new way to understand the pathogenesis of EM. Abstract : FGA enhanced the migration and invasion ability of endometrial stromal cells through RGD sequences binding integrin and activating the FAK/AKT/MMP-2 signaling pathway in endometriosis.